Guidelines for planning, conducting, reporting and evaluating Systematic Reviews in Sport and Health - Teresa Bento (Desafio Singular, 2014)
Reliable summaries of the available evidence are essential to help researchers and practitioners make well-informed decisions. For this reason, the quality of the final result depends on the accuracy in each stage of the development of a systematic review. The aim of the present study is to draw guidelines and recommendations for planning, conducting, reporting and evaluating systematic reviews that support the work of researchers and reviewers. Initially, we address the main characteristics and differences of a systematic review compared to other literature reviews. Then, we describe the main procedures and concerns to be considered in each phase of developing a systematic review. Finally, we present a commented version of a checklist for reporting systematic reviews and guide the reader. We intend to contribute to the set of standards for the structure and quality of knowledge published in review papers, in the fields of Sport and Health, which support more informed decisions.